2020
DOI: 10.3390/ma13092178
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Validity of the Zintl−Klemm Concept for Alkaline-Metal Copper Tellurides by Means of Quantum-Chemical Techniques

Abstract: Understanding the nature of bonding in solid-state materials is of great interest for their designs, because the bonding nature influences the structural preferences and chemical as well as physical properties of solids. In the cases of tellurides, the distributions of valence-electrons are typically described by applying the Zintl−Klemm concept. Yet, do these Zintl−Klemm treatments provide adequate pictures that help us understanding the bonding nature in tellurides? To answer this question, we followed up wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In the cases of the tellurides containing transition-metals, the bonding nature is better described as polar-covalent such that applying the Zintl-Klemm idea to such tellurides could be misleading. [23][24][25][26][27][28] Within the most recent efforts on tellurides comprising posttransition-metals, a new bonding type dubbed 'metavalent' 21,29 or 'hyperbonding' 30 has been proposed. This type of bonding is expected to be at the frontier between entire valence-electron localization as well as delocalization and was introduced based on a portfolio of various quantities, seen both in experiment and calculation.…”
Section: Introductionmentioning
confidence: 99%
“…In the cases of the tellurides containing transition-metals, the bonding nature is better described as polar-covalent such that applying the Zintl-Klemm idea to such tellurides could be misleading. [23][24][25][26][27][28] Within the most recent efforts on tellurides comprising posttransition-metals, a new bonding type dubbed 'metavalent' 21,29 or 'hyperbonding' 30 has been proposed. This type of bonding is expected to be at the frontier between entire valence-electron localization as well as delocalization and was introduced based on a portfolio of various quantities, seen both in experiment and calculation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous explorations [17] typically described lanthanideÀ tellurium bonds as ionic in the spirit of the Zintl-Klemm formalism; however, recent research [18] on tellurides containing lanthanides demonstrated that the bonding nature between lanthanide and tellurium atoms should be depicted as polar-covalent like contacts between transition-metals and post-transition-metal-elements. As the bonding nature of several tellurides containing transition-metals shows such attributes identified for polar intermetallics, [19] it was inferred [20] that these tellurides should be assigned to the family of the polar intermetallics rather than that of the typical Zintl-phase. The bonding nature of polar intermetallics is remarkable, since it falls in a regime between that of the Hume-Rothery phases with metalÀ metal bonding and that of the Zintl-phases with ionic and cluster-based bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the Cu-Cu interactions show a less bonding character relative to the Cu-Te interactions due to the nature of the d 10 -d 10 interactions as typically [98][99][100][101] encountered for homoatomic Cu-Cu contacts. The heteroatomic Cu-Te interactions exhibit a strongly bonding character pointing to a covalent bonding nature with the valence-electrons being located between the copper and tellurium atoms.…”
Section: Resultsmentioning
confidence: 99%